2021
DOI: 10.1016/s2213-2600(20)30579-8
|View full text |Cite
|
Sign up to set email alerts
|

Patient factors and temporal trends associated with COVID-19 in-hospital mortality in England: an observational study using administrative data

Abstract: Background Analysis of the effect of COVID-19 on the complete hospital population in England has been lacking. Our aim was to provide a comprehensive account of all hospitalised patients with COVID-19 in England during the early phase of the pandemic and to identify the factors that influenced mortality as the pandemic evolved. Methods This was a retrospective exploratory analysis using the Hospital Episode Statistics administrative dataset. All patients aged 18 years or older in England who completed a hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
2
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 30 publications
4
102
2
5
Order By: Relevance
“…In descriptive analysis, data were categorised as detailed above and summarised in terms of frequency and percentage. Based on previous work by our team [6], a multilevel (mixed-effects) logistic regression model of patient-related and temporal factors associated with in-hospital mortality was constructed for the current dataset using the 'melogit' command in Stata. A two-level intercept only model was constructed, allowing adjustment for clustering of patients within hospital trusts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In descriptive analysis, data were categorised as detailed above and summarised in terms of frequency and percentage. Based on previous work by our team [6], a multilevel (mixed-effects) logistic regression model of patient-related and temporal factors associated with in-hospital mortality was constructed for the current dataset using the 'melogit' command in Stata. A two-level intercept only model was constructed, allowing adjustment for clustering of patients within hospital trusts.…”
Section: Discussionmentioning
confidence: 99%
“…Age: Categorised as 18À39 years, 40À49 years, 50À59 years, 60À69 years, 70À79 years and 80 years for exploratory analysis and treated as continuous for modelling. The age bands were selected based on previous work in this field by our team and other researchers [10,6].…”
Section: Covariatesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, markedly diverse inpatient mortality rates due to COVID-19 have been reported across different countries [ 38 ]. The extreme straining of many healthcare systems surely has contributed to high mortality rates in some countries especially during the early phases of the pandemic [ 16 , 39 , 40 , 41 ]. Ticinesi et al reported that while COVID-19 patients treated with COVID-19 at an Italian hospital hub during the first weeks of the pandemic were younger and had fewer comorbidities than those admitted between late March and early June 2020, mortality decreased from 27% to 22% [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…A multivariate logistic regression model was used to determine whether presentation during the first versus second wave was an independent predictor for in-hospital mortality. An a priori decision was made to include the variables age ≥ 60 years, male sex, and ACCI in the model since these variables have been previously shown to be important risk factors for mortality in COVID-19 patients [ 16 ]. A log-rank test was used to compare the proportion of patients discharged alive during the first 120 days of hospitalization.…”
Section: Methodsmentioning
confidence: 99%